NETs and oncologic process - E. V. Slukhanchuk (IRBIS LLC, 2021)
Neutrophil Extracellular Traps (NETs) represent the networks consisting of DNA, histones, and proteins produced by activated neutrophils. Such structures have been proved to play a crucial role in inducing neutrophil innate immune response in the pathogenesis of such autoimmune conditions as systemic lupus erythematosus, rheumatoid arthritis, psoriasis, as well as in the pathogenesis of other non-infectious processes, e. g., clotting disorders, thrombosis, diabetes, atherosclerosis, vasculitis and oncology diseases. Recent studies on animal models and human pathologies have uncovered a tremendous role for NETs in tumor progression and metastasis. In this regard, NETs should be considered as pro-oncogenic substances, which further investigation will provide an opportunity to develop new therapeutic strategies.